1995
DOI: 10.1093/nar/23.14.2648
|View full text |Cite
|
Sign up to set email alerts
|

The fat body cell-free system for tissue-specific transcription of plasma protien gene ofBombyx mori

Abstract: A nuclear extract was prepared for the larval fat body of the silkworm, Bombyx mori, and a homologous in vitro system was developed for the transcription of major plasma protein gene of B.mori. The gene for SP1, a storage protein of B.mori, and adenovirus 2 major late (AdML) gene were faithfully transcribed under relatively high template concentrations in the nuclear extract prepared from the fat body of female fifth instar larvae. Complete inhibition of gene transcription by a low concentration of alpha-amani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Fat bodies of fourth instar NP larvae were homogenized and used for isolation of nuclear extract (NE) according to a published method (Mine et al, 1995). Briefly, NE (500 µg in 400 µl) was added to 50 µg (100 µl) of recombinant CpBV-H4 (rCpBV-H4) protein in 500 µl of 100 mM PBS (pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
“…Fat bodies of fourth instar NP larvae were homogenized and used for isolation of nuclear extract (NE) according to a published method (Mine et al, 1995). Briefly, NE (500 µg in 400 µl) was added to 50 µg (100 µl) of recombinant CpBV-H4 (rCpBV-H4) protein in 500 µl of 100 mM PBS (pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, the cells were suspended in five packed cell volumes of buffer C (31) and allowed to swell on ice for 3 min. Nuclei were pelleted and resuspended in 2.2 packed cell volumes of buffer BЈ (31). For lysis, the nuclei were drawn up in a syringe and rapidly pushed through a 26-gauge needle.…”
Section: Establishment Of Nias-bm-f1 and Nias-bm-m1 Cell Linesmentioning
confidence: 99%
“…Extraction of nuclei was carried out on ice for 30 min with constant mixing. After extraction, nuclei were pelleted and the supernatant was dialyzed against buffer DB (31). The dialyzed nuclear protein extracts were then frozen in liquid N 2 and stored at Ϫ80°C.…”
Section: Establishment Of Nias-bm-f1 and Nias-bm-m1 Cell Linesmentioning
confidence: 99%
“…Each 4 pmol of SP1 primer 228 (5′-TATACTCCTTGGCGATCTCC) or 30K6G1 primer 174 (5′-CGGTCTCGTATTCACCAATG) was end-labeled with [γ-32 P]ATP using T4 polynucleotide kinase. Primer extension was carried out using 3 µg of total RNA and each 5′ end-labeled primer (1×10 5 cpm) as described by Mine et al (1995). The synthesized cDNA was separated on 6% acrylamide-7 M urea gel, and radioactivity was detected by autoradiography.…”
Section: Primer Extension Analysismentioning
confidence: 99%
“…Northern blot analyses of the fat body RNA have demonstrated that the biosyntheses of these proteins are regulated in a stage-, tissue-, and sex-dependent manner at the level of gene transcription in fat body cells Sakai et al 1988;Sakurai et al 1988;Fujii et al 1989). Recently, an efficient cell-free transcription system was developed from the nuclear extract of the larval fat body, which preferentially transcribed a homologous storage protein gene in a promoter specific manner (Mine et al 1995).…”
Section: Introductionmentioning
confidence: 99%